Radioprotection of deinococcal exopolysaccharide BRD125 by regenerating hematopoietic stem cells - Park, Hae Ran; Lee, Ji Hee; Ji, Hyun Jung; Lim, Sangyong; Ahn, Ki Bum; Seo, Ho Seong (Frontiers in Oncology, 2022)
There is a substantial need for the development of biomaterials for protecting hematopoietic stem cells and enhancing hematopoiesis after radiation damage. Bacterial exopolysaccharide (EPS) has been shown to be very attractive to researchers as a radioprotectant owing to its high antioxidant, anti-cancer, and limited adverse effects. In the present study, we isolated EPS from a novel strain, Deinococcus radiodurans BRD125, which produces EPS in high abundance, and investigated its applicability as a radioprotective biomaterial. We found that EPS isolated from EPS-rich D. radiodurans BRD125 (DeinoPol-BRD125) had an excellent free-radical scavenging effect and reduced irradiation-induced apoptosis. In addition, bone-marrow and spleen-cell apoptosis in irradiated mice were significantly reduced by DeinoPol-BRD125 administration. DeinoPol-BRD125 enhanced the expression of hematopoiesis-related cytokines such as GM-CSF, G-GSF, M-CSF, and SCF, thereby enhancing hematopoietic stem cells protection and regeneration. Taken together, our findings are the first to report the immunological mechanism of a novel radioprotectant, DeinoPol-BRD125, which might constitute an ideal radioprotective and radiation mitigating agent as a supplement drug during radiotherapy.